REFLEKSI NILAI-NILAI KEARIFAN LOKAL DI BALIK KOMENTAR NETIZEN ATAS KASUS KORUPSI DI GORONTALO: STUDI NETNOGRAFI - Thalib, Mohamad Anwar (Jurnal Riset Ekonomi dan Bisnis Mahasiswa : Brainy, 2025)
The corruption case in Gorontalo has sparked public reaction on social media, which goes beyond spontaneous criticism and reflects local wisdom values. However, previous studies have focused more on public opinion in general without linking it to local cultural philosophies, thus there is a gap in understanding the intersection of local culture and digital discourse. This research formulates the question: what form do the values of local wisdom take behind netizen comments on corruption cases? Using a qualitative method with a netnographic approach, the research locus is on three TikTok videos themed around corruption in Gorontalo. Data was collected thru comment documentation and then analyzed using the interactive Miles & Huberman model. The findings reveal two unique values, namely social empathy (delo wamala lo amango wawu u'unti) and social satire (boututu lo walito), which serve as mechanisms for digital social control. This study offers a new perspective on how local wisdom is reproduced in cyberspace, and recommends integrating cultural values into anti-corruption digital literacy strategies.